Haemorrhoidal artery ligation with and without Doppler guidance in the treatment of haemorrhoidal disease: a single-centre randomized study - P. V. Tsarkov; M. A. Popovtsev; Yu. S. Medkova; A. V. Alekberzade; N. N. Krylov (Сеченовский вестник)
Aim. To evaluate the efficacy of haemorrhoidal artery ligation (HA) with a preliminary palpatory determination of its localization supplemented by mucopexy of haemorrhoids as a new surgical method in the treatment of haemorrhoidal disease (HD) and to compare it with HAL-RAR technology.Materials and methods. The randomized controlled clinical trial included patients over 18 years old with Goligher's grade II, III or IV symptomatic HD. We operated on patients in the study group (n = 75) using palpatory determination of the localization of HA and subsequent mucopexia. In the control group (n = 75) we used HAL-RAR. The primary endpoint (25-30 days after surgery): recurrence rate of HD symptoms. Secondary endpoints: postoperative complication rate, pain intensity on a visual-analogue scale from 1 to 10 points, patient satisfaction with the treatment results on a 10-point scale.Results. According to the initial characteristics (age, gender, body mass index, stage of HD, frequency of clinical symptoms), the groups did not differ. Anal bleeding relapse developed: study group - 11%, control group -14%; relapse of haemorrhoids prolapse: 3% and 5% respectively (p > 0.05). Postoperative complications were noted in 6 (8%) in the study group and 4 (5%) in the control group (p > 0.05). The intensity of pain on the 2nd and 25-30 days after surgery was 6.3 [4.8; 7.4] and 1.2 [0.6; 2.5] points in the study group and 6.5 [4.9; 7.3] and 2.1 [1.9; 4.1] in the control group, respectively (p > 0.05). Patient satisfaction with the treatment results after 12 months was estimated at 8.7 [7.9; 9.2] and 9.4 [8.2; 9.6] in the study and control groups, respectively (p > 0.05).Conclusion. HA ligation with a preliminary palpatory determination of its localization and supplemented with mucopexy of haemorrhoids is no less effective than HAL-RAR in preventing haemorrhoidal bleeding and prolapse of the nodes.